LANGUAGE USE IN ENGLISH COURSE AT HALIM SANUSI UNIVERSITY - Nursidiq, Fajri (Journal of English Education and Teacher Trainer, 2024)
This study aims to investigate the use of language in the English Course at Halim Sanusi University. Besides. It explores students' perception of the tutor’s language in the English classroom at Halim Sanusi University. The method that was used in this study is a descriptive qualitative research method. The subjects were thirteen students of the English Course at Halim Sanusi University. To collect the data, this study used interviews and questionnaires using google form. The result showed the use of language in the English Course at Halim Sanusi was varied enough. Based on the students’ view, the tutor and students used English 35,07%, Indonesian 32,51%, used Sundanese language 8,46%, and mixed language 56,39%. Mix language here was code switching and code mixing. And based on students’ perception of the language use, several students preferred using Indonesian. They realized that the use of Indonesian in the classroom would make them easier to understand the material given. Several students preferred using English than Indonesian. They realized that the use of English in class would make them improve their proficiency in English. They adopted what they found from the teacher’s target language and become comfortable in using the target language too. Additionally, most students perceived that the tutor may mix English and Indonesian equally. They expected that both English and Indonesian are combined and used by the tutor in the classroom interaction. Thus, using English improved their comprehension, while Indonesian were easier for them to understand the materials.